‘A Very Lone Worker’: Woman-Centred Thoughts on Helen Creighton’s Career as a Folklorist - Tye, Diane (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1993)
This paper considers the relationship of gender to Helen Creighton’s work and to her place within Canadian folkloristics. Her conception of folklore techniques — that translated into what and how she collected and how she disseminated those materials — as well as her reception by public and academie audiences, are linked in part to societal and self definitions of appropriate female behavior. As her work is now being evaluated in new ways and admired for its eclecticism, for example, it is clear that those on the margins see things from a different perspective.